The effects of reading medium on children’s and adolescents’ reading comprehension – A two-phased systematic literature review - Friman, Camilla (2025)
Digital devices have developed rapidly and their number as reading media has increased. The effects of reading from a screen on reading comprehension have been studied, but the results have been inconsistent. The aim of this study was to understand how the reading media affects reading comprehension and what are the moderating factors when comparing reading from a paper and reading from a screen. The study was conducted as a two-phased systematic literature review following Fink's seven-step model and PRISMA guidelines. The first phase was an umbrella review of previous meta-analyses and reviews, and the second phase was a systematic literature review of empirical studies. In both phases, the search was conducted in five databases from 2018-2024. Six meta-analyses were identified in the first phase and eleven empirical studies in the second phase. Moderating factors were identified from these studies, which were categorized into three categories: reading related, reader related, and assessment situation related factors. The results showed that the reading media affects reading comprehension, somewhat favoring reading from paper. According to the moderating factors, the results of the study indicate that the phenomenon may be based on individual factors, which is why it is important that the effect of the reading media is taken into account when planning education and testing of competences. The review presents topics for future research.